Inflammation of milk irons methods of comparative equalization of detection - Sapargazieva, A. T.; Zakirova, F. B. (Zhangir khan West Kazakhstan agrarian-technical university, 2017)
Presently an mastitis of cows is actual in West Kazakhstan area.The were conducted the laboratory research studies on the milk sample that took from diary cows caused subclinical and purulent catarrhal mastitis in order to diagnose,as well as data on the effect of mastitis on the chemical composition, organoleptic properties of milk are given in the article.
Наука и образования № 4 (49) 2017 г
Keywords: Inflammation of the mammary gland; Cattle; Diagnostic test; Methods of treatment; subclinical mastitis